FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA AGRIBISNIS OLAHAN HASIL TERNAK PADA PT. CAPSA - Apriliawaty, Nita; Sumartono, Sumartono; Yektiningsih, Endang (Berkala Ilmiah AGRIDEVINA, 2014)
This research aims to: testing the potential of human resources at PT. CAPSA, describe the existing employees at PT. CAPSA, and analyze the most dominant variable affecting the job performance of employees at PT. CAPSA.Methods survey of employees of PT. CAPSA by taking a sample purposively to 30 employees. The collected data were analyzed descriptively and multiple regression.The results showed that the potential of employees in the PT. CAPSA is quite good, in terms of age, gender, length of work and level of education. The employees at PT. CAPSA has a good perception of the company and the variables that affect the performance of employees at PT. CAPSA significantly is the variable age of employees, years of service, and level of education